An Autobiography but Not Quite: The Autobiography of Miss Jane Pittman as a Parody - Rizki Puji Gustian (Universitas Sanata Dharma, 2025)
This article examines Ernest J. Gaines' The Autobiography of Miss Jane Pittman (1972) as a parody and critique of dominant cultural narratives. Combining close reading with biographical criticism, which contextualizes the novel through Gaines’ socio-cultural background as an African American author. Drawing on Bakhtin’s and Hannoosh’s theories of parody and Gates’ concept of chiasmus, the analysis explores how the novel imitates, transforms, and subverts its targets. Bhabha’s notion of mimicry situates parody within postcolonial discourse, while Genette’s theory of frequency analyzes the novel’s repetitive narrative structures. Ashcroft, Griffiths, and Tiffin’s concepts of appropriation and abrogation address Gaines’ use of English, shaped by his identity as a Black writer from Louisiana and his California education. Bakhtin’s heteroglossia highlights the novel’s polyphonic structure, reflecting its diverse voices. Ong’s theories of orality and literacy contrast Louisiana’s oral traditions with Gaines’ literary techniques. Interviews with Gaudet and Wooton reveal the influence of white literary traditions on Gaines, situating him within African American literary frameworks. Loomba’s critique of colonial discourse positions the novel as a subversive response to white supremacy. Thus, the objective of this study is to demonstrate that Gaines uses parody in the Autobiography of Miss Jane Pittman as both a literary form and an ideological tool to challenge hegemonic narratives and amplify African American voices.